Transcranial magnetic stimulation as a new therapeutical approach in autism spectrum disorders and attention deficit hyperactivity disorder – a review - Savino, Rosa; Polito, Anna N.; Ventriglio, Antonio; Bellomo, Antonello; Moscatelli, Fiorenzo; Polito, Rita; Valenzano, Anna A.; Messina, Giovanni; Cibelli, Giuseppe (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Autism spectrum disorders (ASD) and attention deficit hyperactivity disorder (ADHD) neurobiology reveals a complex picture of altered excitation-inhibition balance, aberrant neuronal and neurotransmitter activity, and network disorganization that could be addressed through repetitive transcranial magnetic stimulation (TMS). In this paper, we provide a narrative review of the most recent literature on the use of TMS to treat patients with ASD and ADHD. Material and methods. Literature search from 2018 up to November 2022 has been conducted on PubMed database. Keywords reflected diagnoses and treatment modalities of interest. Analysis of the literature. Eleven clinical trials regarding the use of TMS as a therapeutic tool in ASD, and seven studies (of which 3 are case reports) for ADHD have been reported. The dorsolateral prefrontal cortex (DLPFC) is the most frequent area stimulated. Heterogeneity in stimulation parameters, patient age, and outcome measures limited the interpretation of findings. Conclusion. TMS as a therapeutic tool for neurodevelopmental disorders is still in its infancy. To define the real efficacy of TMS, future studies must be randomized, sham-controlled, and double-blind, and should include a larger sample with adequate inclusion/exclusion criteria, and longitudinal follow-up.
Keywords: ADHD; ASD; autism; neuromodulation; neurodevelopmental disorders; TMS